PERAN FISIOTERAPI DALAM MANAJEMEN KESEHATAN WANITA DENGAN PEMBERIAN EXERCISE ANTENATAL(FUNCTIONAL STABILITY EXERCISE) PADA PENGURANGAN NYERI PANGGUL IBU HAMIL : Physical theraphy,pregnancy,functional stability exercise,pelvic floor,trunk muscles. - Ismaningsih; Sandi Akbar; Siti Muawanah; Nurmaliza Nurmaliza (LPPM Universitas Abdurrab, 2026)
Pregnancy is often accompanied by biomechanical and hormonal changes that can lead to pelvic girdle pain and impact activity limitations and a reduced quality of life for pregnant women. One non-pharmacological approach that can be provided is physiotherapy intervention in the form of functional stability exercise (FSE), which focuses on strengthening the core muscles, pelvic floor muscles, and lumbopelvic stabilizer muscles. This study aims to determine the effect of functional stability exercise on reducing pelvic pain in pregnant women. The type of study used is a quasi-experimental study with a pre- and post-test design without a control group. The study involved 10 pregnant women experiencing pelvic pain and were given FSE intervention for 8 weeks with a frequency of twice daily and 10 repetitions of each exercise.Pain levels were measured using the Verbal Descriptive Scale (VDS) before and after the intervention. Data were analyzed using the Wilcoxon test because the data were not normally distributed. The results showed a significant decrease in pelvic pain levels after the FSE intervention with a p value <0.05. This indicates that functional stability exercise is effective in reducing pelvic pain in pregnant women. Therefore, FSE can be recommended as a safe and effective physiotherapy intervention to help reduce pelvic pain and improve the comfort and functional ability of pregnant women during pregnancy. Keywords: Physical theraphy,pregnancy,functional stability exercise,pelvic floor,trunk muscles.